2023
DOI: 10.1039/d2me00237j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MOF linker rotation and functionalization on methane uptake and diffusion

Abstract: The flexible degrees of freedom in metal–organic frameworks (MOFs) can have significant effects on guest molecule behavior. However, in the majority of studies applying molecular simulations to MOFs, the framework...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…In this study, we investigate competing effects in the behavior of H 2 O and CO 2 adsorbed in CALF-20 using advanced molecular dynamics (MD) simulations carried out with data-driven many-body potential energy functions (PEFs) that accurately predict the properties of water and carbon dioxide , across a wide range of thermodynamic conditions and mixture compositions. CALF-20 is modeled as a flexible framework that can accommodate potential structural changes, which may yield distinct thermodynamic and dynamic properties of guest molecules as concluded in several studies. These simulations allow us to precisely disentangle the competitive adsorption between H 2 O and CO 2 and provide insights at the molecular level, which can inform the design of MOFs specifically optimized for carbon capture applications.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigate competing effects in the behavior of H 2 O and CO 2 adsorbed in CALF-20 using advanced molecular dynamics (MD) simulations carried out with data-driven many-body potential energy functions (PEFs) that accurately predict the properties of water and carbon dioxide , across a wide range of thermodynamic conditions and mixture compositions. CALF-20 is modeled as a flexible framework that can accommodate potential structural changes, which may yield distinct thermodynamic and dynamic properties of guest molecules as concluded in several studies. These simulations allow us to precisely disentangle the competitive adsorption between H 2 O and CO 2 and provide insights at the molecular level, which can inform the design of MOFs specifically optimized for carbon capture applications.…”
Section: Introductionmentioning
confidence: 99%
“…These ghost atoms act as positioning vectors directing the attachment of the selected groups on the organic core structure. The algorithm used to add these chemical groups is similar to that proposed by Yue et al, however, with some notable differences. First, these chemical groups are added in a way that maintains the point group presented by the organic core for the specific geometry of the building block.…”
Section: Resultsmentioning
confidence: 99%
“…However, we generated a CIF for the latter MOF by replacing hydrogen atoms in the CAU-10-H CIF with the functional group NO 2 using molSimplify functionality. 124 Through these steps taken to locate CIFs and prepare them for analysis, we were able to collect adequate CIFs for 181 of the 207 MOFs classified by Burtch et al 41 For the remaining 26 MOFs, no associated CIF structure could be found or the CIF had too much disorder or unusual bond lengths to readily use for featurization. We required CIFs in order to generate ML-ready features that depend on graph connectivity and geometric information of the MOFs.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Where necessary, we removed disordered atoms from CIFs manually and also added missing hydrogen atoms using Mercury 2021.1.0 . Overlapping atoms and floating solvent were removed and functional groups were added using molSimplify 1.7.3. Metal identity modification and functional group addition were necessary in cases where we could not find a CIF for a MOF but could find a CIF for a similar MOF. To generate structures by changing metals in CIFs, we also used Mercury or manual replacement at the command line.…”
Section: Computational Detailsmentioning
confidence: 99%